ANALISIS BIAYA PENGGUNAAN ANTIBIOTIKA PADA BEDAH CESAR DI RUMAH SAKIT PKU MUHAMMADIYAH BANTUL YOGYAKARTA - Faridah Baroroh; Haafizah Dania; Moch. Saiful Bachri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
The use of antibiotics in cesarean surgery is varied, causing the variation of medication costs. The objective of this study was to determine the cost components of direct medical and the antibiotics in surgical Caesarean at PKU Muhammadiyah Bantul-Hospital Yogyakarta. Descriptive observation study along with restropective data was applied as research design.The subjects were patients of cesarean section in the period of 1 January to 31 March 2014 who fullfiled the inclusion criteria. Cost analysis was conducted by Payers Perspective which focused on direct medical costs. The result showed the average of total cost in every surgical cesarean patient was remarked between IDR 7.302.127 to 11.057.450. The highest cost was found in surgical action as of 56.31% - 59.35%. Instead, the cost of pharmaceuticals and the length of hospitalization were noted to be 13.93% - 17.78% and 10.35% - 13,27,35%, respectively. Accordingly, Ceftriaxon-Amoxicillin was the most frequently used antibiotic with the percentage of 63.79%. The pharmaceutical cost of this evidence was 0.26% - 11.77%. The duration of patient hospitalization seems not to contribute any significant impact on the antibiotic cost usage in caesarean surgery (p > 0.05). In term of the surgery, the highest cost was found in surgical act with 56.31% - 59.35% and its pharmaceutical medication due to 13.93% - 17.78% of cost. Herein, the cost of antibiotic was found to be 0.36% - 11.77% from the pharmaceutical charge.